KERJASAMA INTERNASIONAL PENGELOLAAN SEA BED AREA DAN IMPLIKASINYA BAGI NEGARA PANTAI - Heryandi Heryandi (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Science and Ocean Technology rapid development has great impact upon the exploration and exploi-tation growth. This dynamic development shall be followed by empowerment of International Law, therefore, natural resources as the mankind treasure in the sea bed can be protected and managed wisely. International Law has defined rights and duties of each nation, however those rights and du-ties can't be best enforced without good cooperation involving nations and international organiza-tion. Finally, the cooperation shall be based upon the agreement and agreement shall be enforced with good faith. Keywords: international cooperation, regions, sea bed